RELEVANSI NILAI-NILAI TARI BEDAYA BONDHET DALAM PENDIDIKAN KARAKTER - Titik Putraningsih (FBS UNY, 2016)
This research aims to describe the relevance of the values in BedayaBondhetdance course in terms of character education in Dance Education Department,Yogyakarta State University. This research uses descriptive qualitative approach based on written and oral data. The subject of this research is students of Dance Education Department in Faculty of Languages and Arts, year 2014. The steps of this research involve observing, data collecting, interviewing, having written and unwritten documentation, data analyzing, and concluding.The result shows that (1) the relevance of the values in BedayaBondhetdance course in terms of character educationinclude the values of politeness, patience, discipline, concentration, spirit, confidence, determination, cooperation, responsibility, respect, solidarity, consideration, honesty, justice, firmness, feeling of unity, and getting closer to God; and 2) After getting the values ofBedayaBondhet dance the students are expected to have better attitudes and behavior.